Serapan Nitrogen dan Fosfor Tanaman Bunga Matahari yang Dipupuk Urea dan SP-36 pada Tanah Ultisol - Maryati Maryati (Jurnal Agrista, 2007)
Phosphorus and Nitrogen Uptake by Sunflower Due to Urea and SP-36 Fertilization on UltisolABSTRACT. The objective of this research were to study the effect of nitrogen (N) from urea and phosphorus (P) from SP-36 fertilization on N and P uptake by sunflowers (Heliantus annuus L.) on Ultisol.The result of this experiment used was a randomized completely block design arranged in factorial pattern with three replications. The first factor was urea fertilizer (without N, 108.70, 217.40, and 326.10 kg ha-1 urea) and the second factor was P fertilizer (without P, 138.90, 277.80, and 416.70 kg ha-1 SP-36). The result of the experiment showed that, the application of increased urea at various rates of SP-36 affected on soil N total, P available (Bray-1), and yield of sunflowers. Nitrogen and P uptake as well as dry weight of sunflowers by application of 217.40 kg ha-1 urea was higher than without urea. Fertilization of 277.80 kg ha-1 SP-36 had influenced N and P uptake than without SP-36.